2016
DOI: 10.1111/ped.13151
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose Cepharanthin for pediatric chronic immune thrombocytopenia in Japan

Abstract: CEP alone or combined with CS was useful for the management of pediatric chronic ITPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…This is coherent with early studies showing that inhibition of platelet aggregation by CEP is accomplished during the early, membrane-related activation process. A recent study conducted in a pediatric population also underlined the useful effect of CEP for the management of chronic immune thrombocytopenia (Yamazaki et al, 2017).…”
Section: Immuno-modulation -Treatment Of Sepsis Chronic Immune Thrommentioning
confidence: 99%
“…This is coherent with early studies showing that inhibition of platelet aggregation by CEP is accomplished during the early, membrane-related activation process. A recent study conducted in a pediatric population also underlined the useful effect of CEP for the management of chronic immune thrombocytopenia (Yamazaki et al, 2017).…”
Section: Immuno-modulation -Treatment Of Sepsis Chronic Immune Thrommentioning
confidence: 99%
“…In Japan, Cepharanthine has a history of more than 70 years in treating radiation‐related leukopenia (Kanamori et al ., 2016), venomous snakebites (Hifumi et al ., 2013), alopecia areata (Hon and Leung, 2011) and other pathologies. In addition, Cepharanthine displays various bioactivities, including anti‐inflammation (Huang et al ., 2014), anti‐tumour (Shahriyar et al ., 2018) and immune‐modulation (Yamazaki et al ., 2017). The anti‐inflammatory potential of Cepharanthine can be exploited to treat an array of diseases, such as mastitis (Ershun et al ., 2014), acute lung injury (Kao et al ., 2015) and cerebral ischaemia/reperfusion injury (Zhao et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(28) Yamazaki et al were use this drug on 46 chronic-resistant, <16 years Japanese ITP patients. (29) In this study shown cepharantine has used a safe and effective alternative corticosteroidsparing drug. Currently, in refractory cases, successful results have been reported for TPO receptor agonist, romiplostim (30) and eltrombopag (31,32) as a second-line therapy option.…”
Section: Discussionmentioning
confidence: 86%